Ronald Reagan as a Public Speaker: In Search of the Aristotelian Rules of Rhetoric in Selected Addresses Delivered by the 40th US President - Giwojno, Paweł (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The main aim of this paper is to investigate the rhetorical style of Ronald Reagan (1911–2004), both as a President of the United States and as a public speaker. This study is focused on two elements, namely the range of rhetorical devices selected by President Reagan in his selected speeches, as well as a proposed explanation of the use of such devices in the context of a speaker–audience interaction. The latter part of this analysis is centered on the concept of the three persuasive appeals initially defined by Aristotle. In the first part of this paper the concept of the three persuasive appeals (the Aristotelian triangle) is presented and its particular elements explained. Directly afterwards, some theoretical frameworks for the use of linking devices are established. After the theoretical section, three selected Ronald Reagan speeches are analyzed. The focus is on the use of rhetorical devices in the given addresses. Finally, a research conclusion is included with an intention to identify the strategies and the style used by President Reagan in his interaction with the audience. This analysis may be of some help in order to understand how a speaker can powerfully influence listeners by using rhetorical tools.
Keywords: Aristotle; Ronald Reagan; rhetoric; speech